An Updated Guide to Study Polyandry in Social Insects - Rodolfo Jaffé (Universidade Estadual de Feira de Santana, 2014)
In spite of the importance of understanding the adaptive significance of polyandry in the social Hymenoptera (ants, bees and wasps), little consensus exists regarding the terminology employed, the use of different paternity estimates, the calculation of such estimates and their associated error measures, and the way paternity should be treated in comparative studies. Here I summarize previous methodological contributions to the study of polyandry in social insects, hoping that such a compendium will serve as an updated guide to future researchers. I first revise the estimates describing queen mating behavior and paternity outcomes in polyandrous social insects, outlining appropriate methods for calculating them. I then address the errors associated to paternity estimates and explain how to account for them. Finally I discuss in which cases paternity should be treated as a continuous or a categorical variable, and provide an insight into the distribution of paternity across the social Hymenoptera. This technical review highlights the importance of standardizing research methods to prevent common errors, raise confidence in the reported data, and facilitate comparisons between studies, to help shed light into many unanswered questions.